ANALISIS MANAJEMEN RESIKO APLIKASI MYPERTAMINA DENGAN MENGGUNAKAN ISO 31000 - Rahmad Inca Liperda; Urbina Ayu Septia Nieng (INFOTECH journal, 2023)
Digitalization is one of the major trends changing society and business in the near and long term. Digitalization can impact the entire operating environment and internal functions of a company. To increase value added in retail, PT Pertamina Patra Niaga launched the MyPertamina application. Based on data on the number of application users in the Playstore, mypertamina application users have increased. With this increase, many problems must be faced by the company. Therefore, an analysis of risk management is needed to minimize losses that will occur. ISO 31000 is used as a standard for implementing risk management. ISO is considered to have a framework that is straightforward and easily adaptable to companies. This study aims to identify the risks that will occur in using the MyPertamina application and the highest level of risk that must be watched out for and its countermeasures. The results showed that there were 17 identified risks with 3 high-level risks, 8 moderate-level risks and 5 low-level risks. Proposed improvements in this study are prioritized at high levels of risk.